Evaluación de dos sistemas de racionamiento comercial en la alimentación de cerdos en etapa de post destete (31-52 días) en el fundo Miraflores - trópico de San Martín - Rautenberg, Hannes (2016)
The initiators are fundamental to the good performance of the sucker, which meet the energy needs of the same. It is important that these are palatable, easily absorbed and have a high nutritional content, with good management that help you get better weight gains and feed consumption. The aim of this study was to improve pig feed at the stage of rearing (from weaning to 52 days), for which two types of food were used, traditional food from farm and commercial food Pig Tech 2 and Pig Tech 3 was used. the traditional balanced was made in the pigs module of Fundo Miraflores, owned by the National University of San Martin, using 24 piglets Landrace-Yorkshire Duroc 31 days of age of two litters, where two types of food were delivered, one and pelleting other PigTech (Purina), which are divided by 2 steps and their respective days of age: First stage (31-40 days) and Second stage (41-52 days). The 24 piglets will be separated into groups of 4 where a dozen will be provided with the commercial feed (Stage I and Stage II) and the other dozen traditional food (Stage I and Stage II). The food was supplied as directed by the trading company and the University. Food consumption significant difference where in the first stage, the treatment was the highest consumption (5.08 kg) compared with the control (3.50 kg) was found; and for the second stage treatment it was the highest consumption (7.50 kg) compared with the control (6.17 kg). For the initial weight of Stage One significant difference was also found, the greater weight had the witness (6.06kg) comparing to the treatment (4.36 kg); Final weight for the first stage, the treatment got higher gain (8.70 kg) compared with the control (7.14 kg); Final weight for the second stage treatment was higher gain (12.33 kg) compared to the control (8.60 kg). In FCR in the first stage 10 there was also difference, treatment (1.19 kg) was higher than the control (3.75 kg); and in the second stage, the treatment also obtained good result (2.14 kg) compared to the control (5.01 kg). In the cost analysis margin higher with the commercial food utility was found, but is justified by the weight gain and feed conversion. Under the conditions of this study the use of commercial food Pig Tech in weaned piglets is recommended